Improving the safety and quality of milk Volume 2, - Griffiths, Mansel W. (CRC Press, 2010)
Consumers demand quality milk with a reasonable shelf-life, a requirement that can be met more successfully by the milk industry through use of improved processes and technologies. Guaranteeing the production of safe milk also remains of paramount importance. Improving the safety and quality of milk provides a comprehensive and timely reference to best practice and research advances in these areas. Volume 1 focuses on milk production and processing. Volume 2 covers the sensory and nutritional quality of cow's milk and addresses quality improvement of a range of other milk-based products. The health aspects of milk, its role in the diet and milk-based functional foods are the focus of the opening section of Volume 2. Part two reviews essential aspects of milk quality, including milk microbial spoilage and chemical deterioration, sensory evaluation, factors affecting milk vitamin and mineral content and the impact of packaging on quality. Chapters in part three look at improving particular products, such as organic milk, goat milk and sheep milk. The impact of milk on the quality of yoghurt and cheese is also covered. With its distinguished editor and international team of contributors, volume 2 of Improving the safety and quality of milk is an essential reference for researchers and those in industry responsible for milk safety and quality. Examines the sensory and nutritional quality of cow's milk and addresses quality improvement of a range of other milk-based productsReviews the health aspects of milk and its role in the diet, as well as the essential aspects of milk quality, including microbial spoilage and chemical deterioration, sensory evaluation and factors affecting milk vitamin and mineral contentDiscusses various application requirements of milk such as milk quality requirements in yoghurt-making, cheesemaking, infant formulas and applications of milk components in products other than foods.
Keywords: Milk -- Quality.; elektronické knihy; electronic books